1996
DOI: 10.1023/a:1016062224568
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The expected increase in solubility as a function of bile salt concentration can be estimated on the basis of the partition coefficient and aqueous solubility of the compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(84 citation statements)
references
References 21 publications
3
81
0
Order By: Relevance
“…The GastroPlus software includes an estimation of bile salt dependent solubility based on log P according to the equation of Mithani et al [20]:…”
Section: Bile Salt Dependent Solubilitymentioning
confidence: 99%
“…The GastroPlus software includes an estimation of bile salt dependent solubility based on log P according to the equation of Mithani et al [20]:…”
Section: Bile Salt Dependent Solubilitymentioning
confidence: 99%
“…soybean, eggs, sunflower seeds) due to their high surface active properties and biodegradability, these are extensively used in stabilizing oil-water systems. 17 (ii) Saturated lecithins showed higher risk of haemolysis that used in intravenous emulsions when compared with unsaturated lecithins. (i) Semi-synthetic mono-, di-, and triglycerides (MG, DG, and TG) are fractioned glycerides when compared to naturally occurring oils and fats, these have less variability and specified range of acceptability in their compositions.…”
Section: (C) Emulsifiersmentioning
confidence: 99%
“…This is due to the bile acid in the gastrointestinal tract, which plays a key role in the solubilization of poorly soluble compounds and enhances oral absorption. 42) Thus, it is important to evaluate the aqueous solubility contained in the bile acid for poorly soluble compounds because there is the risk that their absorption is strongly affected by the effect of food. In addition, these results demonstrated that JP2-containing 20 mM GCDC was suitable to simulate fluid from fed-state intestine fluid.…”
Section: Takeda Pharmaceutical Co Ltd (Tpc) Approach For Physicochmentioning
confidence: 99%